LncRNA TEX41 promotes the proliferation and migration of squamous cell carcinoma cells by upregulating Atg5 via sponging miR-153-3p: TEX41’s function on SCC - Yang, Wenbo; Chen, Yuyou (Cellular and Molecular Biology, 2023)
This study was conducted to investigate if lncRNA TEX41 could have effects on SCC. The aim was to confirm that TEX41 could promote SCC progression by up-regulating Atg5 via miR-153-3p. TEX41, miR-153-3p, and Atg5 mRNA expression were examined by qRT-PCR. Western blot was used to examine Atg5 protein expression. CCK-8 assay and transwell assay were used to examine SCC cell proliferation and migration. Dual-luciferase reporter assay was used to forecast the binding site of miR-153-3p with Atg5 or TEX41. TEX41 expression was enhanced in SCC tissues and cells. TEX41 knockdown could reduce the SCC cell proliferation and migration. There was a binding site between TEX41 and miR-153-3p, and TEX41 negatively adjusted miR-153-3p in SCC cells. Atg5 was bonded with miR-153-3p, which was adjusted by TEX41. Our study revealed that TEX41 expression was increased in SCC cell lines and tissues. TEX41 could aggravate SCC progression through adjusting the miR-153-3p/Atg5 axis, providing a key target for SCC.